PEMODELAN ARSITEKTUR ENTERPRISE MENGGUNAKAN METODE TOGAF ADM (Studi Kasus: SMAN 1 WATUBANGGA) - Noorhasanah Zain (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
SMA Negeri 1 Watubangga is one of the schools in Kolaka Regency that implement the flagship program, but the current condition of SMA Negeri 1 Watubangga does not have an integrated information system architecture according to the needs and objectives of the school, this problem arises because the school has not focused on the process development of information systems. Therefore it is necessary design of information system architecture SMA Negeri 1 Watubangga. Architectural modeling in this research using TOGAF Framework (The Open Group Architecture Framework) with ADM (Architecture Development Methode) method. Stages used are the preparation of architectural vision, business architecture, information system architecture, technology architecture, opportunities and solutions and migration plans.The result of this enterprise architecture modeling is the blue print model and framework in integrated school information system modeling to support the needs of SMAN 1 Watubangga.